Asthma Counselling Targeted to Removal of Domestic Animals - Louise Hagan; Pierre Valois; Hélène Patenaude; Hélène Boutin; Louis-Philippe Boulet; France Lafrenière (Canadian Respiratory Journal)
OBJECTIVES: To create and evaluate the efficacy of a short individualized educational intervention program, based on Prochaska’s transtheoretical model, for a six-month period in a population of adult asthma patients living with domestic animals but sensitized to these pets.